Ta’awun’s Role in Alleviating Poverty in Makassar City - Zulkarnain Matandra; Abdul Wahab; Syaharuddin Syaharuddin (Universitas Gorontalo, 2020)
This study aims to determine the role of community ta'awun in the city of Makassar in alleviating poverty, and find factors that exist in ta'awun implementation and solutions. This study uses a phenomenological approach as the main approach and assisted pedagogical approach. The results of this study indicate that ta'awun has the opportunity and potential to reduce poverty in the city of Makassar. Ta'awun inhibiting factors of the implementation is poor social ethics, their social stratification and level of understanding of religion is still lacking. As for the solution of these problems is to maximize the role of government, community leaders, and religious leaders in policy, education, and dissemination of the importance ta'awun behavior.